Assessing Functioning across Common Mental Disorders in Psychiatric Emergency Patients: Results from the WHODAS-2. (December 2021) - Hoehne, A.; Giguère, C.-E.; Herba, C. M.; Labelle, R.
Objective: Assessing global functioning in psychiatric emergency settings is important for clinicians to estimate severity of mental disorders, devise a treatment plan, and assess the evolution of their patients' progression over time. The World Health Organization Disability Assessment Schedule-2.0 (WHODAS-2) measures psychological, social, and professional functioning and is recommended as a standardized instrument of choice for use in psychiatric settings. Yet, studies investigating disability profiles of mental disorders using the WHODAS-2 are scarce, and psychometric properties have not been evaluated in a psychiatric emergency context. We describe and compare WHODAS-2 (12-item version) scores across mental disorders (anxiety, mood, psychotic, personality, and substance abuse) in adults admitted to psychiatric emergency. Methods: Data from the Signature Bank were used. Participants admitted to psychiatric emergency completed the WHODAS-2 at admission ( n = 1, 125). Mental disorders were evaluated by psychiatrists, and WHODAS-2 scores were compared across groups. Psychometric properties were evaluated using confirmatory factor analysis (CFA). Results: Higher mean WHODAS-2 scores were reported by those with anxiety, mood, and personality disorders ( P < 0.001) compared to other psychopathologies. The measure showed good internal consistency (global score α = 0.88; domain subscores α = 0.59 to 0.85) and acceptable goodness of fit indices in CFA confirming the original structure of WHODAS-2. Conclusions: Findings from this large-scale study could assist clinicians in interpreting WHODAS-2 scores in psychiatric populations and provide a more detailed portrait of disability profiles associated with different clinical diagnoses.